1994
DOI: 10.21273/jashs.119.3.642
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Tomato Plants Expressing Satellite RNA Are Tolerant to Some Strains of Cucumber Mosaic Virus

Abstract: Transgenic tomato plants (Lycopersicon esculentum Mill.) expressing cucumber mosaic virus (CMV) satellite RNA fused to a gene for β-glucuronidase were produced using Agrobacterium-mediated transformation. The R1 progeny of self-crossed R0 plants were challenge-inoculated with virion or RNA preparations of CMV or tomato aspermy virus (TAV). The transgenic plants challenged with CMV-1 showed mild disease sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…PGPR-mediated biocontrol can be extended to foliar and systemic diseases, even when the PGPRs are applied to seeds and roots (Kloepper et al, 1999). The reduction in virus titre due to the presence of PGPRs and satellite virus agrees with previous results reported by Murphy et al (2003) and McGarvey et al (1994). We observed that both PGPRs and CMV-KU1 strain associated with the viral satellite RNA require a minimum of 3 weeks to establish themselves and provide protection (data not shown).…”
Section: Efficacy Of Using a Combination Of Cmv-ku1 And Pgpr In Enhansupporting
confidence: 88%
“…PGPR-mediated biocontrol can be extended to foliar and systemic diseases, even when the PGPRs are applied to seeds and roots (Kloepper et al, 1999). The reduction in virus titre due to the presence of PGPRs and satellite virus agrees with previous results reported by Murphy et al (2003) and McGarvey et al (1994). We observed that both PGPRs and CMV-KU1 strain associated with the viral satellite RNA require a minimum of 3 weeks to establish themselves and provide protection (data not shown).…”
Section: Efficacy Of Using a Combination Of Cmv-ku1 And Pgpr In Enhansupporting
confidence: 88%
“…The satellite RNA also attenuated CMV-or TAV-indllced symptoms and redllced the accumlllation 01' CMV, but not 01' TA V (HARRISON et a\. 1992;MCGARVEY et al 1994), but nol against TAV-induced disease (MCGARVEY ct al. Similar tolerance to CMV-induced disease and reduction in CMV accumulation was observed when a unit-Iength satellite RNA was expressed transgenically and when CMV was introduced via an aphid vcctor (JACQUEMOND et al 1988).…”
Section: Satellite Biocontrolmentioning
confidence: 99%
“…Thus, a direct application of the satRNA technology was developed in transgenic tomato plants as a protection strategy against CMV. When the same plants were challenged with Tomato aspermy virus, another cucumovirus, they showed satRNA replication but neither helper virus downregulation nor significant tolerance to virus-induced symptoms (McGarvey, Montasser, & Kaper, 1994). Quantitative assays showed that replication of transcript satRNA induced a 10-fold decrease in CMV accumulation in the transgenic tomato plants compared to controls.…”
Section: Satellite Rnamentioning
confidence: 97%